2006
DOI: 10.1002/ffj.1685
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of leaf essential oils from the indigenous ve conifers of Taiwan

Abstract: The chemical composition of leaf essential oils of five conifers in Taiwan were examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 30 publications
(20 reference statements)
3
30
1
1
Order By: Relevance
“…The chemical components of L. petersonii, E. citriodora and M. quinquenervia have been well studied. 8,[21][22] Similar results were obtained in our analysis, although there were some differences in the ratio of chemicals. Ogihara and Takeda 23 previously reported that the essential oil content can vary markedly, depending on growing conditions.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The chemical components of L. petersonii, E. citriodora and M. quinquenervia have been well studied. 8,[21][22] Similar results were obtained in our analysis, although there were some differences in the ratio of chemicals. Ogihara and Takeda 23 previously reported that the essential oil content can vary markedly, depending on growing conditions.…”
Section: Discussionsupporting
confidence: 89%
“…E. citridora and M. quinquenervia revealed weak fungicidal activity, but the other Myrtaceae plant essential oils show no antifungal activity, although antifungal activities of plant essential oils belonging to Myrtaceae have been reported in previous studies. 4,8,[16][17] There are no reports on antifungal activity of L. petersonii and M. quinquenervia essential oils and their components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C. formosensis, known as the Taiwan red cypress, is one of the major forest trees indigenous to the high mountain area of Taiwan [1]. It has a thin bark and pale-pinkish-colored wood and is distributed in mid-elevation (1500 -2150 m above sea level) mountain forests in Taiwan [2]. Kafuka and Ichikawa [3] first reported the chemical composition of C. formosensis.…”
mentioning
confidence: 99%
“…Nghiên cứu về thành phần hóa học tinh dầu lá của loài Sa mộc dầu (C. konishii) ở Đài Loan đã xác định 68 hợp chất với các thành phần chính là -pinen (36,4%), -thujen (11,4%), -eudesmol (8,1%), elemol (5,8%), -elemen (3,5%), -eudesmol (2,8%) và -himachalen (2,7%) [8]. Ở Việt Nam, Trần Huy Thái và nnk.…”
Section: Mở đầUunclassified